Rotation Benefits From N2-Fixing Grain Legumes to Cereals: From Increases in Seed Yield and Quality to Greater Household Cash-Income by a Following Maize Crop - Lengwati, David M.; Mathews, Cherian; Dakora, Felix D. (Frontiers in Sustainable Food Systems, 2020)
We investigated Bambara groundnut, groundnut, mung bean, cowpea, and black gram for use as biofertilizers in cropping systems. The 15N natural abundance technique was used to measure N2 fixation in this study. The percent of N derived from fixation by mung bean (Vigna radiata L. Wilczek), Bambara groundnut (Vigna subterranea L. Verdc.), cowpea (Vigna unguiculata L. Walp.), black gram (Vigna mungo L.), and groundnut (Arachis hypogaea L) was 98, 83, 79, 66, and 45% respectively. Nitrogen contribution from these legumes was 83, 67, 39, 36, and 32 kg.ha−1 respectively for Bambara groundnut, groundnut, mung bean, black gram, and cowpea. Maize grain yield without N fertilizer was 2,449, 2,291, 2,204, 2,046, and 1,671 kg.ha−1, respectively, for maize following groundnut, Bambara groundnut, cowpea, mung bean, black gram, and maize. Grain yield increase of maize after legumes without N fertilizer was 47, 46, 37, 32, and 22%, respectively, for groundnut, Bambara groundnut, cowpea, mung bean, and black gram. Supplying 0 to 60 kg N ha−1 to maize plants increased shoot DM from 3,264 to 4,279 kg.ha−1, grain yield from 2,184 to 3,586 kg.ha−1, and whole-plant DM from 5,448 to 7,865 kg.ha−1, which represented a 31, 64, and 44% increase with N fertilizer supply from 0 to 60 kg N ha−1. Symbiotic N benefit of preceding legumes to maize without N fertilizer was 20–40 kg N. ha−1 in fertilizer equivalents. The preceding legumes increased maize grain concentrations of P, Ca, S, Fe, Mn, and Zn in zero-N plots relative to maize after maize. There was a 225, 222, 154, 149, and 108% increase in marginal returns of maize after groundnut, Bambara groundnut, cowpea, mung bean, and black gram, respectively, without N fertilizer.